Evaluating Pore Space in Macroporous Ceramics with Water‐Based Porosimetry. Issue 6 (28th February 2013) - Andersson, Linnéa; Larsson, Per Tomas; Wågberg, Lars; Bergström, Lennart
Abstract : We show that water‐based porosimetry (WBP), a facile, simple, and nondestructive porosimetry technique, accurately evaluates both the pore size distribution and throat size distribution of sacrificially templated macroporous alumina. The pore size distribution and throat size distribution derived from the WBP evaluation in uptake (imbibition) and release (drainage) mode, respectively, were corroborated by mercury porosimetry and X‐ray micro‐computed tomography (μ‐CT). In contrast with mercury porosimetry, the WBP also provided information on the presence of "dead‐end pores" in the macroporous alumina.